Benefit of an association of an antioxidative substrate and a traditional chinese medicine on telomere elongation - M'kacher, Radhia; Breton, Ludovic; Colicchio, Bruno; Puget, Henry; Hempel, William M.; Al Jawhari, Mustafa; Jeandidier, Eric; Frey, Michel (Cellular and Molecular Biology, 2019)
Telomere shortening is involved in age-related disorders, such as cancer and cardiovascular diseases. Recently, telomerase re-activation strategies have been proposed to counteract telomere shortening and its consequences. Here, we investigated the benefit of dietary supplementation with a mix of S-adenosyl-methionine (SAMe) and a polysaccharide extract of Astragalus (APS) on telomere length of circulating lymphocytes of healthy volunteers. Blood lymphocytes of a cohort of 26 healthy volunteers who were administrated the mix of SAMe and APS in a food supplement for one year were collected. In vitro treatment of blood lymphocytes of healthy volunteers with the mix was also performed. A cohort of 150 healthy volunteers was used as a control. Telomere length was measured by Q-FISH. The micronucleus assay was performed to detect genotoxicity of the mix. The telomeres of circulating lymphocytes of the cohort of 26 donors supplemented with the mix were significantly longer than those of matched controls (p < 10-4). This elongation was essentially observed in the lymphocytes of older donors. Similarly, in vitro treatment of circulating lymphocytes with the mix significantly increased telomere length and decrease the proportion of cells with short telomeres. Here, we observed an increase in telomere length after in vivo and in vitro administration of a mix with SAMe and APS. The benefit of dietary supplementation with this mix opens a new horizon for the battle against aging and could be used in the treatment of chronic age-related disorders.